Advances in the treatment of acne scars - Zhang, Meng; Liu, Chunmei; Zhang, Shengni; Chu, Ruiqi; Ren, Xiangxiang (Frontiers in Medicine, 2025)
Acne vulgaris and its resulting scars represent common clinical dermatological concerns. Even after the resolution of active lesions, scars can cause significant psychological distress and severely impair patients' quality of life. In recent years, advancements in medical technology have led to the clinical application of various innovative therapies for acne scar management, with the primary goals of effectively improving both the aesthetic appearance and functionality of the scars. Treatment strategies continue to be refined—ranging from traditional physical modalities (such as microneedling) to modern energy-based devices (such as fractional lasers)—to balance efficacy and safety. Current research focuses on developing combination therapy approaches. The integration of chemical peels, laser technologies, and dermal fillers is emerging as a key trend for the future, aiming to enhance treatment outcomes while reducing treatment burden.